Observation of CuPt and CuAu I-type ordered structure in HgCdTe grown by isothermal vapour phase epitaxy - Aguirre, Myriam H. (2003)
Ordered structures, CuPt and CuAu I types in HgCdTe are reported for the first time. Hg1-xCdxTe thin crystals were grown by isothermal vapour phase epitaxy (ISOVPE) method on a CdTe substrate and they were observed by transmission electron microscopy (TEM) in planar view and cross-sectional geometries. Two variants of CuPt-type ordered structure were found in different microdomain sets on HgCdTe. Another superstructure observed was the CuAu I-type coexisting with CuPt domain structure.